PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KOMITMEN ORGANISASIONAL DAN KINERJA KARYAWAN - Anak Agung Sagung Shinta Damayanthi; Desak Ketut Sintaasih (Forum Manajemen STIMI Handayani Denpasar, 2016)
Occupational health and safety are important aspects which should benoted the company, so that employees avoid the risk of accidents at work, especiallyin companies that are vulnerable to the risk of accidents and occupational health.The purpose of this study was to describe the effect of health and safety on theorganizational commitment and performance of employees. The study was conductedat PT. Dewata Gassari Denpasar, with a sample of 81 employees as respondents.Data were analyzed using path analysis. The results showed that safety and healthpositive and significant impact on organizational commitment. Work safety andoccupational health are also positive and significant impact on employee performanceand organizational commitment has a positive and significant effect on employeeperformance. These results provide evidence that the better the company facilitatesemployees with occupational health and safety program, it will be able to push theorganizational commitment of employees, and ultimately improve performance.